2017
DOI: 10.1111/imj.13387
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to clinical pathways in the management of suspected pulmonary embolus: are there cost implications?

Abstract: This study investigated the cost implications of poor compliance to established guidelines for management of suspected pulmonary embolism (PE) in two NSW public hospitals. A retrospective audit showed that the prevalence of PE overall was 9.9% (4.3% in the low-risk groups) in 436 patients. An estimated total of $32 454 (14%) was spent on unnecessary tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We did not evaluate patients’ pretest probability for PE as part of this study, which may have led to inclusion of higher risk patients for PE. While D‐dimer testing has been validated for use in patients with a low to moderate pretest probability using an evidence‐based decision rule, 37 prior studies have demonstrated inconsistency of this practice in the clinical setting and so our findings may be more representative of actual clinical practice 38,39 . Our quasi‐experimental study design was used to estimate the causal effect of the intervention and as such may be subject to unmeasured confounding 40 .…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not evaluate patients’ pretest probability for PE as part of this study, which may have led to inclusion of higher risk patients for PE. While D‐dimer testing has been validated for use in patients with a low to moderate pretest probability using an evidence‐based decision rule, 37 prior studies have demonstrated inconsistency of this practice in the clinical setting and so our findings may be more representative of actual clinical practice 38,39 . Our quasi‐experimental study design was used to estimate the causal effect of the intervention and as such may be subject to unmeasured confounding 40 .…”
Section: Limitationsmentioning
confidence: 99%
“…While D-dimer testing has been validated for use in patients with a low to moderate pretest probability using an evidence-based decision rule, 37 prior studies have demonstrated inconsistency of this practice in the clinical setting and so our findings may be more representative of actual clinical practice. 38,39 Our quasi-experimental study design was used to estimate the causal effect of the intervention and as such may be subject to unmeasured confounding. 40 We addressed this limitation using segmented regression analysis of an interrupted time series that included a robust preintervention phase.…”
Section: Limitationsmentioning
confidence: 99%
“…Because of nonspecific symptoms, which may suggest another condition, the diagnosis of PE might be challenging in real-life practice. Despite subsequent updates of the clinical guidelines and statements released by international societies dealing with VTE [3,4], the diagnostic pathways in case of suspected APE in everyday practice are still burdened with numerous errors [5][6][7]. Undiagnosed APE leads to death, chronic thromboembolic pulmonary hypertension, disability, and worsening of quality of life.…”
Section: Introductionmentioning
confidence: 99%